2016
DOI: 10.1007/s11099-015-0174-6
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological responses of Eichhornia crassipes (Mart.) Solms to As<sup>5+</sup> under different stress conditions

Abstract: Arsenic is a critical contaminant that is released into the environment through geochemical processes and anthropic actions. Two independent hydroponic experiments were performed to evaluate the ecophysiological responses of water hyacinth [Eichhornia crassipes (Mart.) Solms] to As under various stress conditions. In experiment 1, water hyacinth was exposed to As 5+ at concentrations of 0, 0.2, 2.0, and 20 mg L -1 for 0, 2, and 4 d; in experiment 2, water hyacinth was exposed at concentrations of 0, 0.025, 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Detrimental effects of pollutants (As 5+ ) on gas exchange of E. crassipes have been reported, and show that higher pollutant concentrations significant decrease F v /F m , variable chlorophyll fluorescence (F v /F 0 ) and pigment content; however, lower concentrations of pollutant did not affect these processes (Meneguelli‐Souza et al . 2016). Pereira et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detrimental effects of pollutants (As 5+ ) on gas exchange of E. crassipes have been reported, and show that higher pollutant concentrations significant decrease F v /F m , variable chlorophyll fluorescence (F v /F 0 ) and pigment content; however, lower concentrations of pollutant did not affect these processes (Meneguelli‐Souza et al . 2016). Pereira et al .…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to those of Meneguelli‐Souza et al . (2016) and Lin & Jin (2018). Our results also indicate that Cu 2+ negatively affects photosynthetic electron transport efficiency of E. crassipes , as also found by Faseela et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there was no significant change in the total Chl content of the three species among different water depth treatments (Figure 4A). The maintenance of the photosynthetic pigment concentration (Chl concentration) explains the stability of F v/ F m (Meneguelli-Souza et al, 2016). These results suggested that 2 m or 3 m water depths did not cause damage to these three macrophytes, because they can tolerate a wide range of water depths (Vöge, 1994; Carrillo et al, 2006; Zhu et al, 2012; Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, other reports contradict this finding. Meneguelli-Souza et al (2016) observed that q P and q N decreased significantly in water hyacinth (Eichhornia crassipes) on day 4 after treatment in the presence of 2.0 and 20 mg(As 5+ ) L -1 . Tanyolac et al (2007) found that both q P and q N showed decreasing trends in maize leaves exposed to 1.5 mM Cu for 12 d. Those authors suggested that the observed decrease in q N might be associated with the AOS generation caused by Cu stress.…”
Section: Treatment Time [D]mentioning
confidence: 92%